Strategi Pemilihan Influencer Marketing Onitsuka Tiger Indonesia pada Pagelaran Milan Fashion Week Autumn/Winter 2023 - Panji Putra Sutanto; Eka Yusup; Weni Adityasning Arindawati (Journal of Management and Bussines (JOMB), 2024)
This research aims to analyze the marketing influencer selection strategy for Onitsuka Tiger Indonesia at the Milan Fashion Week Autumn/Winter 2023 show with the aim of changing the brand image from a sports brand to a fashion brand. The research method used is qualitative with a descriptive approach. Data collection techniques include observation, face-to-face and virtual in-depth interviews, documentation, and literature study. The results of this research highlight the strategic process for selecting Onitsuka Tiger Indonesia's influencer marketing, which accommodates several factors such as availability of influencer schedules, budget considerations, and ease of collaboration. Alyssa Daguise was chosen as a marketing influencer collaborating with Onitsuka Tiger Indonesia because she has a French passport so she doesn't need a visa, apart from that, collaboration abilities and schedule availability were also taken into consideration. In conclusion, this research provides insight into the influencer marketing selection strategy in changing the brand image from a sports brand to a fashion brand. Keywords: Influencer Marketing, Milan Fashion Week, Onitsuka Tiger Indonesia